FACTORS ASSOCIATED WITH DELAY IN TUBERCULOSIS MANAGEMENT IN SARAWAK, MALAYSIA - Md Mizanur, Rahman; Andrew, Kiyu; Ahmad Hafiz, Mohamad (Malaysian Public Health Physician's Association, 2022)
Delay in Tuberculosis (TB) management is a public health concern that leads to unfavourable treatment outcomes. The delays could come from the patients or the health care facilities. This study aimed to determine TB management in terms of delays in diagnosis and treatment initiation among TB patients in Sarawak, Malaysia. Thiscross-sectional study was conducted among adult TB patients through face-to-face interviews using adapted and validated questionnaires. Seven hundred twenty-four patients were selected using a systematic random sampling method from 17 TB clinics in Sarawak. Data entry and analysis were done by IBM SPSS Version 22.0. The median duration of patient, diagnostic and treatment delay was 1080 days, 61 days, and two days, respectively. The multivariate binary logistic regression analysis revealed that the university level of education (p<.05) and visiting healthcare facilities four times and above (p<.001) appeared to be statistically significantly associated with patient delay. In diagnostic delay, female, moderate family stigma (p<.01), multiple visits to a healthcare facility (p<.001) were found to be significant factors. However, age 50-59 years, ethnicity, primary and secondary level of education (p<.01), TB knowledge (p<.05), number of symptoms, the action was taken (p<.001), been advised (p<.01), and investigations during the first visit (p<.05) were significantly associated with treatment delay. Though the study did not depict the national scenarios of overall delays in TB management, the factors identified in this study would be policy options to reduce thedelays in the initiation of future TB management.